Treatment of chronic presacral sinus after low anterior resection. (24th June 2013) - Sloothaak, D. A. M.; Buskens, C. J.; Bemelman, W. A.; Tanis, P. J.
Abstract Aim The aim of this retrospective study was to determine patient and treatment characteristics with corresponding clinical outcome of symptomatic chronic presacral sinus after low anterior resection. Method Twenty‐two patients were treated for a presacral sinus persisting for at least 12 months after low anterior resection for rectal carcinoma between January 2005 and March 2012. Patient charts were reviewed and analysed using descriptive statistics. Results Fistula formation was the most frequently observed secondary complication in 55% of patients. A median of 6 (1–44) surgical, endoscopic or radiological interventions related to the presacral sinus were performed. Overall, the chronic presacral sinus healed after multimodality treatment in nine (41%) patients at a median interval from primary surgery of 45 (24–93) months. If basic treatment principles were followed (anastomotic reconstruction or completion proctectomy with filling of the cavity), healing rate of the sinus was higher than where these principles were not adhered to (62% vs 11%). Conclusion Successful treatment of a chronic presacral sinus after low anterior resection appears to be achieved by salvage surgery with anastomotic reconstruction in highly selected patients or intersphincteric completion proctectomy and omentoplasty.